LEARNING SINGING METHODS TO DEVELOP THE ABILITY TO MEMORIZE HADITH FOR CHILDREN AGED 5-6 YEARS RA ULUL ALBAB JEMBER - Ria Octa Viana; Riris Wahyuningsih; Maria Qori’ah (International Conference on Humanity Education and Society (ICHES), 2023)
The singing method is an educator's effort to carry out a learning strategy plan that has been prepared by providing learning materials through verses containing material so that children feel happy and carefree, because if the child's mood is happy and joyful then the knowledge given by the educator to the child will be easily accepted and understood. especially in group B applying the singing method in learning to develop memory memorizing hadith. Considering that memorization activities are activities that tend to be monotonous and difficult for students, RA Ulul Albab Jember teachers innovate in providing learning that can make participants didik feels carefree, happy, excited and easy to understand the material, namely using the singing method to develop memory memorizing hadith. If the material is given by the singing method and given continuously, the material will be recorded in the child's brain and moreover, the child can with easy to memorize. This method is still relatively rarely applied in other institutions.